USULAN PERAWATAN MESIN STITCHING DENGAN METODE RELIABILITY CENTERED MAINTENANCE - Kurniawan, Rizki Arga; Kholik, Heri Mujayin (Department Industrial Engineering, University of Muhammadiyah Malang, 2015)
Based on industrial competition nowadays, production quality occurs to be the main concern of severals top companies. Method of machine maintenance is a way to incresing their production quality. Nowadays, several companies still using a corrective maintenance to maintain their machine, which is all of machine maintenance only be performed if the machine damaged. This thesis only focus to high frequency stitching machine. This thesis using Reability centered maintenance method to obtain optimum maintenance interval. This method gathers 7 step of data processing, starting from data selection, determinating restricions of the system, descripting the system and function of block diagram, and then FMEA (Failure Mode Effect Analysis) and LTA (Logic Tree Analysis). The result of this method is a correct maintenance action for critical components that included in condition directed and time directed categories. Qulitative analysis for Reliability Centered Maintenance method includes types indectification of maintenance, cause of damage and the occuring failure. Resul of the research contain several maintenance actions for critical components using condition directed method and critical component replace schedule using time directed method. From the suggested system maintenance simulation with RCM method, downtime can be decrease until 47,83%.